Polyamine pathways interconnect with GABA metabolic processes to mediate the low-temperature response in plants - Xu, Mengyun; Yang, Qinwen; Bai, Genxiang; Li, Ping; Yan, Jian (Frontiers in Plant Science, 2022)
Low temperatures are among the most commonly encountered environmental conditions that adversely affect plant growth and development, leading to substantial reductions in crop productivity. Plants have accordingly evolved coordinated mechanisms that confer low-temperature adaptation and resistance. The plant metabolic network, including polyamines (PAs) and γ-aminobutyric acid (GABA) is reprogrammed to ensure that essential metabolic homeostasis is maintained in response to cold stress conditions. Additionally, GABA might serve as a central molecule in the defense system during low-temperature tolerance in plants. However, our understanding of how these metabolites function in conferring cold tolerance is still far from complete. Here, we summarized how PAs and GABA function in conferring cold tolerance, and describe the crucial role of GABA in the mitigation of ROS during cold stress in plants.